2014
DOI: 10.3899/jrheum.140100
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Chest Radiography for the Diagnosis of Tuberculosis (TB) and Its Role in the Detection of Latent TB Infection: a Systematic Review

Abstract: In this systematic review we evaluate the role of chest radiography (CXR) in the diagnostic flow chart for tuberculosis (TB) infection, focusing on latent TB infection (LTBI) in patients requiring medical treatment with biological drugs. In recent findings, patients scheduled for immunomodulatory therapy with biologic drugs are a group at risk of TB reactivation and, in such patients, detection of LTBI is of great importance. CXR for diagnosis of pulmonary TB has good sensitivity, but poor specificity. Radiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 83 publications
0
51
0
3
Order By: Relevance
“…In the small group of UMRs assessed here, no cases of active tuberculosis were identified by chest x-ray, which is a standard screening tool for active pulmonary tuberculosis for migrants coming to Germany. Although some authors describe that the sensitivity of gamma-interferon release assays is higher than that of chest x-ray for the diagnosis of active pulmonary tuberculosis in sputum-negative patients [24], a recent literature review indicated that chest x-rays have acceptable to good sensitivity for the diagnosis of pulmonary tuberculosis [25]. Further, the positive predictive value of gamma-interferon release assays for the diagnosis of active tuberculosis is low for patients from high-endemicity settings because positive results can also be expected in cases of latent or cured tuberculosis [24].…”
Section: Discussionmentioning
confidence: 99%
“…In the small group of UMRs assessed here, no cases of active tuberculosis were identified by chest x-ray, which is a standard screening tool for active pulmonary tuberculosis for migrants coming to Germany. Although some authors describe that the sensitivity of gamma-interferon release assays is higher than that of chest x-ray for the diagnosis of active pulmonary tuberculosis in sputum-negative patients [24], a recent literature review indicated that chest x-rays have acceptable to good sensitivity for the diagnosis of pulmonary tuberculosis [25]. Further, the positive predictive value of gamma-interferon release assays for the diagnosis of active tuberculosis is low for patients from high-endemicity settings because positive results can also be expected in cases of latent or cured tuberculosis [24].…”
Section: Discussionmentioning
confidence: 99%
“…The use of chest radiography (CXR) for the diagnosis of pulmonary TB (PTB) dates back over a century 3 . However, the utility of CXR is limited by modest specificity, high hardware costs, and poor inter-rater reliability [4][5][6] . In addition, many high burden countries, including India, suffer from a lack of qualified radiologists to interpret CXR 7 .…”
mentioning
confidence: 99%
“…An anteroposterior chest X-ray is one of the most important tests to be performed in a patient having TB or suspected TB. Chest X-ray findings include parenchymal infiltrates, hilar adenopathy, cavitation, nodules and pleural effusion [14]. Infiltrates or consolidations and cavities are often seen at the lung upper lobes, with or without mediastinal or hilar lymphadenopathy.…”
Section: Chest X-raymentioning
confidence: 99%